THE ROLE OF INNOVATIVE TECHNOLOGIES IN SOCIETY - qizi, Makhmatkulova Hikoyat Ghiyosiddin; qizi, Kholdarova Fotima Mahammadjon (Journal of Contemporary Business Law & Technology: Cyber Law, Blockchain, and Legal Innovations, 2024)
This topic discusses the significance of innovative educational technologies in contemporary times. It provides information about the role of modern methods and technologies during the course of lessons.